Role of Single Procalcitonin Test on Admission as a Biomarker for Predicting the Severity of Clostridium difficile Infection - Hamo, Zohar; Azrad, Maya; Nitzan, Orna; Sagie, Asaf; Tkhawkho, Linda; Binyamin, Dana; Peretz, Avi (Frontiers in Microbiology, 2017)
Objective: To evaluate whether serum Procalcitonin (PCT) at the early stage of infection can serve as a potential biomarker for determining Clostridium difficile infection (CDI) severity. Methods: Fifty-four patients diagnosed with CDI were enrolled in the study. Serum samples were obtained within a median time of 24-48 hours of the lab result for presence of C. difficile. PCT levels were measured by chemiluminescence immunoassay. Demographic, clinical, and prognostic data concerning the patients were retrospectively collected from medical records. The illness severity score was determined according to "Score indices for Clostridium difficile infection severity". Results: We found that serum PCT levels were significantly higher in patients with moderate disease, compared to patients with mild disease (p=0.0032). Additionally, PCT was correlated with mortality (p=0.0002), white blood cell (WBC) count (p=0.019), and community-acquired disease (p=0.0345). Conclusions: Early measurement of PCT may serve as a biomarker for early prediction of CDI severity, which is of great importance due to the high risk of complications and death.